Irbesartan Attenuates Atherosclerosis in Watanabe Heritable Hyperlipidemic Rabbits: Noninvasive Imaging of Inflammation by F-Fluorodeoxyglucose Positron Emission Tomography - Yan Zhao; Keita Fukao; Songji Zhao; Ayahisa Watanabe; Tadateru Hamada; Kazuaki Yamasaki; Yoichi Shimizu; Naoki Kubo; Naoyuki Ukon; Toru Nakano; Nagara Tamaki; Yuji Kuge (Molecular Imaging)
The purpose of this study was to assess the usefulness of 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) in evaluating the antiatherogenic effects of irbesartan, an angiotensin II type 1 receptor blocker. Watanabe heritable hyperlipidemic rabbits were divided into the irbesartan-treated group (75 mg/kg/d; n = 14) and the control group ( n = 14). After a 9-month treatment, rabbits underwent 18 F-FDG PET. Using the aortic lesions, autoradiography and histologic examinations were performed. PET imaging clearly visualized the thoracic lesions of control rabbits and showed a significant decrease in the 18 F-FDG uptake level of irbesartan-treated rabbits (78.8% of controls; p < .05). Irbesartan treatment significantly reduced the plaque size (43.1% of controls) and intraplaque macrophage infiltration level (48.1% of controls). The 18 F-FDG uptake level in plaques positively correlated with the plaque size ( r = .65, p < .05) and macrophage infiltration level ( r = .57, p < .05). Noninvasive imaging by 18 F-FDG PET is useful for evaluating the therapeutic effects of irbesartan and reflects inflammation, a key factor involved in the therapeutic effects.